Orbitofrontal Cortex and Olfactory Bulb Volume Predict Distinct Aspects of Olfactory Performance in Healthy Subjects - Seubert, Janina; Freiherr, Jessica; Frasnelli, Johannes; Hummel, Thomas; Lundstroem, Johan N. (Cerebral Cortex, 2013)
While recent studies suggest an important role of higher order olfactory brain areas for basic olfactory performance, the extent to which cortical and peripheral neural markers account for separate portions of the variability in olfactory perceptual acuity is still unclear. We addressed this question by correlating voxel-based morphometry data from 90 healthy adults with olfactory performance measures. Supplementing this approach with region of interest (ROI) analyses of functionally defined olfactory cortical regions and olfactory bulb volume, we sought to disentangle the relative contribution of central and peripheral areas to behavioral variability. Whole-brain analyses revealed a significant positive correlation of gray matter volume and olfactory function scores in the right orbital sulcus. This effect was confirmed by the ROI analyses, which further indicated a significant association of the olfactory score with olfactory bulb volume. Moreover, a functional dissociation was observed, with central and peripheral mechanisms explaining different aspects of the observed behavioral variance in the olfactory subscores. In line with previous clinical studies, these data thus suggest an important role of regional gray matter volume in the right orbitofrontal cortex and olfactory bulb volume for olfactory performance in healthy individuals.
Keywords: OFC; olfaction; olfactory bulb; perception; VBM